Metabolism Regulation by Estrogens and Their Receptors in the Central Nervous System Before and After Menopause - Coyoy, A.; Guerra-Araiza, C.; Camacho-Arroyo, I. (Hormone and Metabolic Research, 2016)
Estrogens through their intracellular receptors regulate various aspects of glucose and lipid metabolism. The effects of estrogens in metabolism can be mediated by their receptors located in different areas of the brain such as the hypothalamus, which is involved in the control of food intake, energy expenditure, and body weight homeostasis. Alterations in the metabolic regulation by estrogens participate in the pathogenesis of the metabolic syndrome and cardiovascular diseases in women. The metabolic syndrome is an important disease around the world, consisting in a combination of characteristics including abdominal obesity, dyslipidemia, hypertension, and insulin resistance. It increases the risk of cardiovascular disease and type 2 diabetes. It has been suggested that there is an increase in the incidence of metabolic syndrome during menopause due to estrogens deficiency. Estrogens replacement improves insulin sensitivity and reduces the risk of diabetes in rats. In the brain, estrogens through the interaction with their receptors regulate the activity of neurons involved in energy homeostasis, including appetite and satiety. Thus, estradiol and their receptors in the hypothalamus play a key role in metabolic syndrome development during menopause.
Keywords: metabolic syndrome; menopause; estrogens receptor; diabetes